The Wire Devils - Packard, Frank L. (Frank Lucius), 1877-1942 (Book collections on Project MUSE., 2013)
The Wire Devils follows a criminal gang of the same name who hijack a railroad's telegraph lines to glean information about profitable shipments. Combining elements from dime-store novels and Frank L. Packard's own experience on the rails, this is at once a hybrid western and a thriller still worth reading nearly a century after it was written.